From Mass Medium to Niche Medium: Advertising in American Comic Books, 1934–2014 - Bart Beaty; Benjamin Woo (Comicalités, 2021)
This paper draws on the study of 42,248 advertisements contained in the What Were Comics? corpus to analyze the transformation of the status of the American comic book between 1934 and 2014. We argue that sustained attention to patterns of advertising in American comic books challenges the dominant historiography of the publishing format. We suggest that the history of the American comic book can be understood in terms of four general periods: 1) a period of domestication during which time it was understood that the primary audience for comic books was children; 2) a period of crisis in the industry in the late-1950s brought on by the loss of the child reader; 3) a period of transition marked by smaller and lower-value advertising targeting a mixed readership of children and adults; and, 4) a period of equilibrium in which advertising is split between national brands and in-house advertisements.